(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Bardet-Biedl Syndrome (BBS) is a rare autosomal recessive ciliopathy presenting with diverse clinical features, including retinal dystrophy, obesity, post-axial polydactyly, learning disabilities, hypogonadism, and renal abnormalities. Early diagnosis is challenging due to its gradual progression and overlap with other disorders, especially in settings where genetic testing is limited. We report four Bangladeshi cases demonstrating variable phenotypic expressions of BBS. All patients exhibited progressive visual loss, obesity, and polydactyly, along with additional manifestations such as diabetes mellitus, dyslipidemia, hypogonadism, renal impairment, developmental delay, and behavioral issues. Diagnosis was made using Beales’ clinical criteria, with each patient fulfilling multiple primary and secondary features. Management required multidisciplinary input from endocrinology, ophthalmology, nephrology, and mental health services, integrating lifestyle intervention, pharmacotherapy, and family counseling. This case series underscores the clinical heterogeneity of BBS, the importance of early clinical recognition, and the need for coordinated multidisciplinary care to optimize long-term outcomes. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 66-72]